2011
DOI: 10.1029/2011jd015637
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of black carbon in East Asia estimated from observations at a remote site in the East China Sea

Abstract: [1] East Asia, including China, is the largest source of anthropogenic black carbon (BC). In estimating the BC emissions from this region, it is advantageous to use BC mass concentrations measured at remote locations on the ocean appropriately distant from the large sources because of spatially uniform distributions through mixing during transport. We made continuous measurements of the BC mass concentration with an accuracy of about 10% at Cape Hedo on Okinawa Island, Japan, in the East China Sea, from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(130 citation statements)
references
References 36 publications
8
121
1
Order By: Relevance
“…They concluded that Chinese annual anthropogenic BC emission is 1.92 TgC yr −1 , similar to the 1.81 TgC yr −1 estimated by Zhang et al (2009). Both Hakami et al (2005) and Kondo et al (2011) used observations far downwind from China during particular seasons, thus they may not reflect the total annual emissions from the entire country. Matsui et al (2009) simulated EC and OC in northern China in summer 2006 using anthropogenic emissions similar to those estimated by Zhang et al (2009).…”
Section: T-m Fu Et Al: Carbonaceous Aerosols In Chinamentioning
confidence: 65%
See 2 more Smart Citations
“…They concluded that Chinese annual anthropogenic BC emission is 1.92 TgC yr −1 , similar to the 1.81 TgC yr −1 estimated by Zhang et al (2009). Both Hakami et al (2005) and Kondo et al (2011) used observations far downwind from China during particular seasons, thus they may not reflect the total annual emissions from the entire country. Matsui et al (2009) simulated EC and OC in northern China in summer 2006 using anthropogenic emissions similar to those estimated by Zhang et al (2009).…”
Section: T-m Fu Et Al: Carbonaceous Aerosols In Chinamentioning
confidence: 65%
“…Kondo et al (2011) measured BC concentration on a remote island in East China Sea and selectively analysed data strongly influenced by transport from China (mostly in spring and winter of the years 2008 and 2009). They concluded that Chinese annual anthropogenic BC emission is 1.92 TgC yr −1 , similar to the 1.81 TgC yr −1 estimated by Zhang et al (2009).…”
Section: T-m Fu Et Al: Carbonaceous Aerosols In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of recently published studies for China reported rather high BC, e.g. about 1.8 Tg was estimated by Zhang et al (2009) Kondo et al (2011) for 2008 using a top-down approach; these results and other recent regional studies are marked with black star symbols in Fig. 10 and included in Table S8.1.…”
Section: Comparison With Other Studiesmentioning
confidence: 96%
“…BC particles are usually in the sub-micron size range (e.g., Petzold et al, 2005;Schwarz et al, 2008;Kondo et al, 2011) contributing only little to PM 2.5 and PM 10 as these are often dominated by other particle types. In the following, we therefore focus on the contribution of BC to PM 1 .…”
Section: Particulate Matter and Aerosol Optical Depthmentioning
confidence: 99%